2019
DOI: 10.3390/cancers11050702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cellular Death Pathways after mTHPC-mediated Photodynamic Therapy (PDT) in Five Human Cancer Cell Lines

Abstract: One of the most promising photosensitizers (PS) used in photodynamic therapy (PDT) is the porphyrin derivative 5,10,15,20-tetra(m-hydroxyphenyl)chlorin (mTHPC, temoporfin), marketed in Europe under the trade name Foscan®. A set of five human cancer cell lines from head and neck and other PDT-relevant tissues was used to investigate oxidative stress and underlying cell death mechanisms of mTHPC-mediated PDT in vitro. Cells were treated with mTHPC in equitoxic concentrations and illuminated with light doses of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 85 publications
0
41
0
Order By: Relevance
“…Essentially, the exogenous ROS induced by this cold photochemical reaction are the most important and first effector molecules of PDT, although they also depend on the intracellular oxygen levels most of the time. In addition to exogenous ROS, PDT-induced ROS can also cause intracellular metabolic changes, induce endoplasmic reticulum stress[ 12 ], and/or destroy mitochondrial potential[ 13 ] to increase endogenous ROS production. On the one hand, the photochemical reaction directly caused by PDT produces a short ROS duration (< 0.05 μs), with high reactivity and a limited diffusion distance (< 0.02 μm)[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, the exogenous ROS induced by this cold photochemical reaction are the most important and first effector molecules of PDT, although they also depend on the intracellular oxygen levels most of the time. In addition to exogenous ROS, PDT-induced ROS can also cause intracellular metabolic changes, induce endoplasmic reticulum stress[ 12 ], and/or destroy mitochondrial potential[ 13 ] to increase endogenous ROS production. On the one hand, the photochemical reaction directly caused by PDT produces a short ROS duration (< 0.05 μs), with high reactivity and a limited diffusion distance (< 0.02 μm)[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasonable agreement between the calculated spectroscopic properties also constitutes a further validation of the novel force field, with an obvious improvement over the parametrization used in our previous work. 61 Note that experimental results have been conducted in ethanol instead of water, 104,105 because of the global low solubility of the sensitizers. In the simulations, we decided to use water as a solvent to mimic the most biologically relevant solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al 31 indicated that inhibition of autophagy enhanced sinoporphyrin sodium mediated-PDT (DVDMS-PDT) induced apoptosis in CRC cells, indicating that autophagy was protective in DVDMS-PDT-treated CRC cells. In addition, Lange et al indicated that m-THPC-PDT could induce cell death and autophagy in human cancer cells, and found that autophagy might occur in parallel to apoptosis or that autophagy might be dominant, eventually resulting in autophagy-associated apoptosis 47 . Huang et al 43 revealed that inhibition of autophagy decreased the apoptosis induced by pyropheophorbide-α methyl ester-mediated PDT in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%